The Concept of Freedom according to the Communitarianism Trend - Salman, Ihsan Abdulhadi; Abdalla, Shahab Ahmed (Journal of Legal and Political Studies, 2023)
The authenticity of the Communitarianism trend, as a political philosophy, lies in its direct focus on a range of differences related to freedom, society and democracy, and its attempt to unite the values of society with the democratic values of personal freedom and equality. Its ideal is a democratic society. This trend was proposed as a revisionist current of post liberalism, taking its form from the flaws and excesses of liberalism and its individualist doctrine. Its purpose is to place the welfare of societies rather than personal freedom at the center of their attention, by consolidating the values of society in the public sphere, rather than maximizing individualism and absolute freedom, because the accelerating pace of social change in the past few decades has now moved society with its problems to the center of political discourse. Accordingly, the groups defined their concept of freedom through their analysis of society, and believe that the concept of individual freedom should be analyzed from the perspective of society as well. With this perception, the collectivist tendency becomes less inclined than liberals to worry about deprivation of personal freedom, in the name of the common good and the common good. Their basic argument is that if an individual wants to enjoy his freedom, he must abide by the boundaries, regulations and goals of the society in which he lives. From this perception, they defined freedom as a concept that has a relative meaning, not an absolute. Any search for freedom outside the framework of society is futile.
Keywords: Freedom; Communitarianism; authenticity; philosophy; democracy